(untitled) (Dhaka University Journal of Science, 2017)
Community facilities are found to play an important role to improve the health status of children in many developing countries. In this paper, an attempt has been made to examine whether community facilities have impact on the nutrition status of under-five children in Bangladesh using ordinal logistic regression model. Data extracted from Bangladesh Demographic and Health Survey (BDHS), 2011 have been used for the purpose of analysis. Though unadjusted impact of community facilities on nutrition status of children was found be significant, it diminishes when controlled for demographic and socio-economic factors. Dhaka Univ. J. Sci. 65(1): 27-33, 2017 (January)